P-Glycoprotein Mediates Efflux Transport of Darunavir in Human Intestinal Caco-2 and ABCB1 Gene-Transfected Renal LLC-PK1 Cell Lines - Hiromi Fujimoto; Maiko Higuchi; Hiroshi Watanabe; Yasuhiro Koh; Arun K. Ghosh; Hiroaki Mitsuya; Naomi Tanoue; Akinobu Hamada; Hideyuki Saito (2009)
Darunavir (DRV) is a nonpeptidic protease inhibitor (PI) approved for the treatment of human immunodeficiency virus (HIV) infection. DRV displays potent activity against HIV strains resistant to other available PIs. Coadministration with ritonavir (RTV) improves the oral bioavailability of DRV. Inhibition of cytochrome P450 by RTV has been proposed as a mechanism for enhanced DRV bioavailability. However, interaction of these drugs with intestinal transporters has not been elucidated. This study was performed to explore the involvement of P-glycoprotein in transcellular DRV transport in monolayers of human intestinal Caco-2 and in ABCB1 multidrug resistance 1, (MDR1) gene-transfected renal LLC-PK1 (L-MDR1) cell lines. Transepithelial transport of DRV in Caco-2 cell monolayers was 2-fold greater in the basal-to-apical direction compared to that in the opposite direction. RTV had a significant inhibitory effect on the efflux transport of DRV in Caco-2 cells. The apical-to-basal DRV transport was enhanced by P-glycoprotein inhibitors, cyclosporin A and verapamil, as well as multidrug resistance-related protein (MRP/ABCC) inhibitors, probenecid and MK571. Using the L-MDR1 cell line, basal-to-apical DRV transport was much greater than in the opposite direction. Furthermore, cyclosporin A markedly inhibited the basal-to-apical DRV transport. RTV significantly increased the apical-to-basal transport of DRV in L-MDR1 cells, but reduced transport in the opposite direction. DRV inhibited P-glycoprotein-mediated efflux of calcein-acetoxymethyl ester in L-MDR1 cells with the inhibitory potency of 121 μM. These findings suggest that DRV is a substrate of P-glycoprotein and MRP, most likely MRP2. RTV appeared to inhibit P-glycoprotein, thereby enhancing the absorptive transport of DRV.